Pak Lah dan pendidikan - Mohd Zuber Zain; Abdul Halim Ali; Raja Ahmad Shalaby (Universiti Pendidikan Sultan Idris, 2005)
Biography and contributions of Abdullah bin Haji Ahmad Badawi, Malaysian Prime Minister on Malaysian education.